Relationships between Harmonic Characteristics and Different Types of Voltage Source - Risnidar C Risnidar C; I. Daut I. Daut; Syafruddin H Syafruddin H; Yusniati Yusniati (Universitas Ahmad Dahlan, 2012)
This paper discusses about harmonic characteristics due to different types of voltage sources. Ideal voltage source is sinusoid, unfortunately in actual condition load receives voltage sources from elements which produce the non sinusoidal output voltage, and consequently, the load has non pure sinusoid waveform as an input voltage. Voltage source at power of common coupling (PCC) between transformer and linear load and nonlinear load has become an example of the case. This research has been conducted by using Schhafner Power Quality Analyzer and PM300 Power Quality Analyzer, which was focused to figure out all characteristics related to harmonics such as power, voltage, current, power factor (p.f.), Harmonic Distortion, and harmonic energy losses cost. The selected load is induction motor with Adjustable Speed Drive (ASD) because this typical load is one of electronic device that causes harmonics. The voltage sources in this research are sine wave, square wave and harmonic order combinations of 3rd, 5th and 7th which can create from Schhafner Power Quality Analyzer.